The very short hydrogen bond in the pyridine N-oxide - trichloroacetic acid complex: an inelastic neutron scattering and computational study - Stare, Jernej (Acta chimica slovenica, 2011)
We have investigated the dynamics of the very short hydrogen bond (RO...O = 2.430 A) of the pyridine N-oxide trichloroacetic acid complex in the solid state by combining vibrational spectroscopy using inelastic neutron scattering with extensive computational studies and analysis of the vibrational spectra. The Density Functional Theory (DFT) computational models used ranged from the isolated gas phase cluster to three approaches with periodic boundary conditions, namely CRYSTAL, CPMD and VASP, all of which, however calculate frequencies in the harmonic approximation. While all but the gas phase calculation yield structural parameters for the hydrogen bond in reasonable agreement with experiment, only the periodic VASP and CPMD approaches resulted in INS spectra (calculated with the program a-climax) that adequately reproduced some of the key features of the experimental spectrum related to the in-plane and outof-plane bending modes of the H-bond. No clear indication was found either in experiment or computational studies for OH stretching. More sophisticated and time-consuming calculations are therefore indicated to elaborate on the hydrogen bond dynamics including molecular dynamics simulations or the use of quantum dynamics on multidimensional potential energy surfaces.
Keywords: analizna kemija; harmonic analysis; inelasting neutron scattering; kvantna dinamika; molekulska dinamika; neelastična nevronska vibracijska spektroskopija; periodic DFT calculations; short hydrogen bonding; vibrational dynamics; vodikova vez